Zinc negative electrode with super-hydrophobic and zinc-philic monomolecular layer and preparation method and application of zinc negative electrode
By forming superhydrophobic and zinc-philic monomolecular layers on the surface of the zinc negative electrode, the problems of zinc negative electrode instability and zinc ion transport are solved, and the efficient stability and electrochemical performance of zinc ion batteries are achieved, which are suitable for large-area industrial production.
Patent Information
- Application Number
- CN202411688068.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-03
AI Technical Summary
The instability, hydrogen evolution reaction, corrosion and dendrite growth of zinc negative electrodes in aqueous zinc ion batteries lead to low zinc utilization and stability, and the existing hydrophobic interface construction methods are complex and are not conducive to large-scale industrial production.
Using the zinc negative electrode preparation method of superhydrophobic and zinc-philic monolayers, single molecules with Si-O-Si and Si-O-M covalent bonds are formed on the surface of zinc metal by self-assembly technology of metal ion plating solution and fluorosilane dispersion. layer, inhibits corrosion of active water molecules and improves zinc ion transport kinetics.
It significantly improves the stability and electrochemical performance of zinc negative electrodes, extends the cycle life of zinc-zinc symmetrical batteries, improves the efficiency and cycle stability of Coulomb, and simplifies the preparation process, which is suitable for large-area industrial production.
Smart Images

Figure CN119253091A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aqueous zinc ion batteries, and in particular to a zinc negative electrode with a super-hydrophobic and zinc-philic monomolecular layer, and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries (AZIBs) are considered to be very promising large-scale energy storage systems due to their excellent safety, low cost and environmental friendliness. However, the unstable zinc anode / electrolyte interface, hydrogen evolution reaction, corrosion, dendrite growth and other problems in the zinc anode have seriously reduced the utilization and stability of zinc, limiting the application of AZIBs.
[0003] So far, strategies such as introducing self-adsorbing additives into the electrolyte or constructing a hydrophobic protective layer on the surface of the zinc negative electrode can effectively alleviate the side reactions caused by active water molecules on the zinc surface, thereby improving the stability of the zinc negative electrode interface. However, the transport of zinc ions in aqueous electrolytes is mainly carried out in the form of hydrated zinc ions. While the hydrophobic interface hinders the active water molecules, it may also reduce the transport of hydrated zinc ions, resulting in hysteresis in the transport kinetics of zinc ions and reducing the rate performance of aqueous zinc ions; and because the volume of the zinc electrode changes greatly during repeated electroplating / stripping, the hydrophobic interface may rupture and peel off from the electrode, resulting in re-contact between the zinc metal and the electrolyte, causing side reactions and the growth of dendrites, and ultimately leading to battery failure. In addition, the construction process of most hydrophobic interfaces is currently complex and cumbersome, which is not conducive to large-scale industrial production. Therefore, it is crucial to use a simple and rapid method to prepare a stable hydrophobic and zinc-philic interface on the surface of the zinc negative electrode to improve the performance of zinc ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a zinc negative electrode with a super-hydrophobic and zinc-philic monolayer, and a preparation method and application thereof, which can not only effectively inhibit the corrosion of active water molecules to metal zinc, improve the utilization rate and stability of the zinc negative electrode, but also effectively promote the desolvation process of hydrated zinc ions, accelerate the transmission dynamics of zinc ions and reduce the interface impedance, and significantly improve the electrochemical performance of the battery. In addition, the self-assembly process of the single molecule is simple and easy, which is conducive to large-scale industrial production.
[0005] In a first aspect, the present invention provides a method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer, the method comprising:
[0006] A metal ion plating solution is prepared, and zinc metal is immersed in the metal ion plating solution, and then the zinc metal is taken out, and repeatedly washed and dried to obtain zinc metal modified with metal nanoclusters;
[0007] A fluorosilane dispersion is prepared, and the zinc metal modified by the metal nanoclusters is immersed in the fluorosilane dispersion. Then the zinc metal is taken out, and repeatedly washed and dried to obtain a zinc negative electrode with a super-hydrophobic and zinc-philic monolayer.
[0008] According to the above-mentioned preparation method, a zinc negative electrode with a high-roughness surface modified with metal nanoclusters is obtained by immersing zinc metal (such as zinc foil) in a metal ion plating solution; then the zinc containing the structure is immersed in a fluorosilane dispersion, and the spontaneous assembly characteristics of fluorosilane molecules are used to generate a dense monolayer containing covalent bonds such as Si-O-Si and Si-OM on the surface of the rough zinc. After the self-assembly is completed, it is repeatedly washed with anhydrous ethanol and placed in a vacuum oven to dry, thereby obtaining a zinc metal negative electrode with super hydrophobicity and zinc-philic monolayer modification.
[0009] Furthermore, the solute of the metal ion plating solution includes at least one of copper sulfate, indium chloride, tin tetrachloride and silver nitrate, and the concentration of the metal ion plating solution is 0.1-0.5 mol / L.
[0010] Furthermore, in the step of immersing the zinc metal in the metal ion plating solution, then taking out the zinc metal, and repeatedly washing and drying to obtain the zinc metal modified with metal nanoclusters:
[0011] The soaking time is 1 to 1800 seconds, the drying time is 0.5 to 6 hours, and the oven temperature is 40 to 100°C.
[0012] Furthermore, the solute of the fluorosilane dispersion includes at least one of tridecafluorooctyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, and 1H,1H,2H,2Hperfluorooctyltrimethoxysilane, and the concentration of the fluorosilane dispersion is 0.01 to 0.2 mol / L.
[0013] Further, in the step of immersing the zinc metal modified by the metal nanoclusters into the fluorosilane dispersion, then taking out the zinc metal, repeatedly washing and drying, to obtain a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer:
[0014] The soaking time is 1 to 600 seconds, the drying time is 0.5 to 4 hours, and the oven temperature is 40 to 80°C.
[0015] Furthermore, the solvent of the fluorosilane dispersion includes at least one of ethanol, isopropanol, toluene, xylene, ethyl acetate, butyl acetate, acetone, and methyl ethyl ketone.
[0016] Furthermore, the super hydrophobic, zinc-philic monolayer is a chemically bonded modified layer.
[0017] In a second aspect, the present invention further provides a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer, which is prepared according to the above-mentioned preparation method.
[0018] In a third aspect, the present invention further proposes an application of the zinc negative electrode having a super-hydrophobic and zinc-philic monolayer in an aqueous zinc ion battery, the application comprising:
[0019] preparing a positive electrode sheet;
[0020] preparing an electrolyte;
[0021] The positive electrode sheet, Whatman glass fiber separator, electrolyte and zinc negative electrode with super hydrophobic and zinc-philic monolayer are assembled into a battery.
[0022] Furthermore, the step of preparing the positive electrode sheet includes:
[0023] Ammonium vanadate, manganese dioxide, iodine, vanadium pentoxide, or polyaniline and polytetrafluoroethylene (PTFE) are mixed in a mass ratio of 8:1:1 to prepare a slurry and rolled onto a stainless steel mesh with a mesh size of 300. After drying at 80°C in air overnight, the positive electrode sheet is obtained by rolling;
[0024] The step of preparing the electrolyte comprises:
[0025] Dissolve ZnSO4·7H2O or Zn(OTf)2 in deionized water to prepare an electrolyte with a concentration of 1 to 5 mol / L.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. The present invention provides a method for preparing a super-hydrophobic and zinc-philic monolayer for zinc negative electrode protection and its application. The monolayer can effectively inhibit the corrosion of active water molecules to metal zinc, accelerate the transmission kinetics of zinc ions, significantly improve the stability and reversibility of metal zinc, and greatly improve the coulombic efficiency and cycle life of the battery. -2 、1mAh cm -2 At current density and capacity of 5 mA cm, the zinc-zinc symmetric battery assembled with this zinc anode can stably cycle for more than 2400 h, and the polarization voltage is as low as 19 mV; even at 5 mA cm -2 , 5mAh cm -2 At high current density and high surface capacity, the zinc-zinc symmetric battery can still stably cycle for more than 1200h. The ammonium vanadate soft-pack battery assembled with the zinc negative electrode can also be used at a current density of 1A g -1 The initial specific capacity under the conditions of -1, and it can still maintain 76.1% of its capacity after 200 cycles. This work provides a new solution for the preparation of high-stability zinc anodes.
[0028] 2. The present invention uses a simple and rapid molecular self-assembly technology to modify low surface energy fluorosilane on the surface of the zinc negative electrode with high surface roughness. The monolayer prepared by this method can be chemically bonded to the negative electrode surface and can stably exist even under conditions such as bending, folding, and twisting, and has excellent interface stability. The molecular self-assembly technology can be carried out directly in the air without the need for an inert gas environment and heating treatment. The preparation process is simple and easy, which is conducive to large-scale industrial production.
[0029] 3. The present invention uses a simple and rapid self-assembly technology to chemically bond ultra-low surface energy perfluorosilane to the surface of the zinc negative electrode treated with surface roughening, effectively inhibiting the side reactions induced by active water molecules, and significantly improving the stability of the zinc negative electrode; and the ultra-thin zinc-philic monolayer can promote the zinc ion transfer kinetics and reduce the interface resistance, which is beneficial to the zinc deposition of dendrites and the improvement of rate performance. In addition, the monomolecular protective layer can greatly improve the electrochemical performance of aqueous zinc ion batteries, and the preparation process is simple and easy, suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 It is a schematic flow chart of a method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to the present invention;
[0032] Figure 2 is a graph showing the relationship between the assembly time and the contact angle of the zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention;
[0033] Figure 3 This is a digital photograph of the change in hydrophobicity of the zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention after being deformed and destroyed by folding, bending, etc.;
[0034] Figure 4 Schematic diagram of a water drop bouncing experiment and a sliding angle test of a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention;
[0035] Figure 5 This is a schematic diagram of an experimental test of a zinc negative electrode with a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention under a water flow impact test;
[0036] Figure 6These are different magnifications of ordinary zinc (all on top), copper nanocluster-modified zinc (all in the middle), and a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer (all on the bottom) in Example 1 of the present invention under a field emission scanning electron microscope;
[0037] Figure 7 is a transmission electron microscope image of a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention;
[0038] Figure 8 This is the impedance Nyquist diagram of a zinc-zinc symmetric battery assembled with a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention;
[0039] Fig. 9 The zinc-zinc symmetric battery assembled with the zinc negative electrode having super hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention is -2 ,1mAh cm -2 Electrochemical performance diagram under test conditions;
[0040] Fig.10 The zinc-copper battery assembled with the zinc negative electrode having super hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention is -2 ,1mAh cm -2 Electrochemical performance diagram under test conditions;
[0041] Fig.11 The ammonium vanadate soft-pack full battery assembled with the zinc negative electrode having super-hydrophobic and zinc-philic monolayer prepared in Example 1 of the present invention has a high conductivity at 1A g -1 Electrochemical performance diagram under test conditions. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0043] The following detailed description is an exemplary description, which is intended to provide further detailed description of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used in the present invention are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention.
[0044] Example 1
[0045] At room temperature, 16.5 g of copper sulfate powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M copper sulfate plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the copper sulfate solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0046] Add 500ul of heptadecafluorodecyltrimethoxysilane to anhydrous ethanol to prepare a 0.1M heptadecafluorodecyltrimethoxysilane dispersion, soak the metal nanocluster-modified zinc metal in the heptadecafluorodecyltrimethoxysilane dispersion, take out the zinc metal after 20s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode with a superhydrophobic and zinc-philic monolayer.
[0047] Example 2
[0048] At room temperature, 16.5 g of copper sulfate powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M copper sulfate plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the copper sulfate solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0049] Add 500ul of tridecafluorooctyltrimethoxysilane to anhydrous ethanol to prepare a 0.1M tridecafluorooctyltrimethoxysilane dispersion, soak the metal nanocluster-modified zinc metal in the tridecafluorooctyltrimethoxysilane dispersion, take out the zinc metal after 20s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode with a super-hydrophobic and zinc-philic monolayer.
[0050] Example 3
[0051] At room temperature, 16.5 g of indium chloride powder was dissolved in a deionized water solution, stirred evenly, and a 0.2 M indium chloride plating solution was prepared. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the indium chloride solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0052] Add 500ul of dodecafluoroheptylpropyltrimethoxysilane to isopropanol to prepare a 0.1M dodecafluoroheptylpropyltrimethoxysilane dispersion, soak the metal nanocluster-modified zinc metal in the dodecafluoroheptylpropyltrimethoxysilane dispersion, take out the zinc metal after 30s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode with a superhydrophobic and zinc-philic monolayer.
[0053] Example 4
[0054] At room temperature, 16.5 g of tin tetrachloride powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M tin tetrachloride plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the tin tetrachloride solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0055] Add 500ul of 1H,1H,2H,2Hperfluorooctyltrimethoxysilane to acetone to prepare a 0.1M 1H,1H,2H,2Hperfluorooctyltrimethoxysilane dispersion, soak the zinc metal modified with metal nanoclusters in the 1H,1H,2H,2Hperfluorooctyltrimethoxysilane dispersion, take out the zinc metal after 20s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode with a superhydrophobic and zinc-philic monolayer.
[0056] Example 5
[0057] At room temperature, 16.5 g of tin tetrachloride powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M tin tetrachloride plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the tin tetrachloride solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0058] Add 500ul of heptadecafluorodecyltrimethoxysilane to anhydrous ethanol to prepare a 0.1M heptadecafluorodecyltrimethoxysilane dispersion, soak the metal nanocluster-modified zinc metal in the heptadecafluorodecyltrimethoxysilane dispersion, take out the zinc metal after 20s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode with a superhydrophobic and zinc-philic monolayer.
[0059] Comparative Example 1
[0060] At room temperature, 16.5 g of copper sulfate powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M copper sulfate plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was soaked in the copper sulfate solution. The zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a zinc negative electrode containing only copper nanoclusters.
[0061] Comparative Examples 2-4 are basically the same as Example 1, except that only the solute of the fluorosilane dispersion is adjusted to 3,3,3-trifluoropropyltriethoxysilane, triethoxy(1H,1H,2H,2H-nonafluorohexyl)silane, and triethyl(trifluoromethyl)silane, respectively.
[0062] Comparative Example 5
[0063] At room temperature, 16.5 g of silver nitrate powder was dissolved in a deionized water solution and stirred evenly to prepare a 0.2 M silver nitrate plating solution. A metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was immersed in the silver nitrate solution, and the zinc metal was taken out after 30 seconds, washed repeatedly, and then placed in an oven and dried at 80°C for 2 hours to obtain a metal nanocluster-modified zinc metal.
[0064] Add 500ul of heptadecafluorodecyltrimethoxysilane into anhydrous ethanol to prepare a 0.1M heptadecafluorodecyltrimethoxysilane dispersion, soak the metal nanocluster-modified zinc metal in the heptadecafluorodecyltrimethoxysilane dispersion, take out the zinc metal after 30s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode.
[0065] Comparative Example 6
[0066] At room temperature, a metal zinc sheet with a size of 4 cm × 6 cm × 0.01 cm was etched in a 0.1 M dilute hydrochloric acid solution. After 30 seconds, the zinc metal was taken out, washed repeatedly, and then placed in an oven and dried at 80 ° C for 2 hours to obtain metal nanocluster-modified zinc metal.
[0067] Add 500ul of heptadecafluorodecyltrimethoxysilane into anhydrous ethanol to prepare a 0.05M heptadecafluorodecyltrimethoxysilane dispersion, soak the zinc metal with a rough surface in the heptadecafluorodecyltrimethoxysilane dispersion, take out the zinc metal after 10s, wash it repeatedly, and then place it in an oven and dry it at 60°C for 2h to obtain a zinc negative electrode.
[0068] Depend on Figure 2 It can be seen that the super-hydrophobic monolayer structure can be quickly prepared within ten seconds. Figure 3 It can be seen that the zinc negative electrode with super hydrophobic and zinc-philic monolayer prepared in Example 1 can be stably present under conditions such as bending, folding, and twisting. Figure 4 It can be seen that the super-hydrophobicity of the monolayer on the surface can completely isolate water, making it difficult for water droplets to spread and shrink into a sphere, and the sliding angle is less than 3°. Figure 5 It can be seen that the monolayer also exhibits excellent self-cleaning properties, with water bouncing off the surface, keeping it clean, due to Figure 7 It can be seen that the transmission electron microscopy results show that the thickness of the modified organic layer is only 1.95nm, which is a monomolecular layer.
[0069] The zinc negative electrode with super hydrophobic and zinc-philic monolayer prepared in Example 1 was observed using a field emission electron microscope. Figure 6 As shown, copper is uniformly dispersed on the zinc surface in the form of nanoclusters.
[0070] Test Example 1
[0071] A zinc-zinc symmetric battery was assembled in air: a Whatman separator was used and the electrolyte was 2 mol / L zinc sulfate. The zinc-zinc symmetric battery assembled with the zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 was used as an experimental sample, and the zinc-zinc symmetric battery assembled with the zinc negative electrode modified with copper nanoclusters prepared in Comparative Example 2 was used as a control group. The interfacial resistance of the battery before and after cycling was measured by electrochemical impedance spectroscopy (EIS). Figure 8 As shown, the battery impedance matched with pure zinc assembly is 550Ω, the battery impedance matched with copper nanocluster zinc assembly is 90Ω, and the battery impedance matched with superhydrophobic monolayer zinc assembly is 60Ω, which are significantly lower than those of the two control batteries.
[0072] Test Example 2
[0073] A zinc-zinc symmetric battery was assembled in air: a Whatman separator and an electrolyte of 2 mol / L zinc sulfate were used. The zinc-zinc symmetric battery assembled with the zinc negative electrode having a super-hydrophobic and zinc-philic monolayer prepared in Example 1 was used as an experimental sample, and a zinc-zinc symmetric battery assembled with the zinc negative electrode modified with copper nanoclusters prepared in Comparative Example 1 was used as a control group. The assembled symmetric battery was charged at a current density of 1 mA cm -2 , with a capacity of 1 mAh cm -2 The charge and discharge test is carried out under the conditions of Fig. 9 As shown; In contrast, the long cycle stability of the matching super-hydrophobic monolayer zinc negative electrode battery prepared in Example 1 is more excellent, and can be stably cycled for up to 2400h, and the battery polarization degree is small, with an overpotential of only 19mV, which shows that Zn 2+ It can be transmitted quickly at the electrode / electrolyte interface; while the overpotentials of zinc negative electrode batteries matching pure zinc and copper nanoclusters are 41mV and 23mV, respectively, and they can only cycle for 300h and 740h before short-circuiting and failing.
[0074] Test Example 3
[0075] Assemble the full battery in air: Mix ammonium vanadate with oxalic acid, add the powder to 70 ml of deionized water, stir until a uniform solution is formed, and heat the solution in a 100 mL Teflon reactor at 140 ° C for 18 h. After the reaction is completed, collect the precipitate, wash it repeatedly with deionized water, use isopropanol as a dispersant, mix the obtained powder with Ketjen black (KB) and polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1 to prepare a slurry and roll it on a stainless steel net with a mesh size of 300. After drying at 80 ° C in air overnight, a slurry containing 3-4 mg cm -2The NVO electrode was then rolled to obtain the positive electrode. A Whatman diaphragm and an electrolyte of 2 mol / L zinc sulfate were used as the electrolyte. The ammonium vanadate full battery assembled with the zinc anode having super-hydrophobicity and zinc-philic monolayer prepared in Example 1 was used as the experimental group, and an ammonium vanadate full battery assembled with pure zinc without any modification and the zinc anode modified with copper nanoclusters prepared in Comparative Example 1 was used as the control group. The above-assembled full battery was charged at a current density of 1A g -1 The charge and discharge test is carried out under the conditions of Fig.11 As shown; in comparison, the long cycle stability of the matching super-hydrophobic monolayer zinc negative electrode battery prepared in Example 1 is more excellent, and the initial specific capacity is 158.1 mAh g -1 After 1500 cycles, it can still maintain 92.3% of its capacity, while the battery matched with pure zinc has a capacity retention rate of 0% after 500 cycles; the capacity retention rate of the zinc negative electrode battery matched with copper nanoclusters is 9.7% after 1500 cycles. This shows that the superhydrophobic monolayer can improve the interfacial stability of the zinc negative electrode, inhibit the side reactions mediated by water, and improve the electrochemical performance of the whole battery.
[0076] Test Example 4
[0077] Ammonium vanadate and oxalic acid were mixed in air, the powder was added to 70 ml of deionized water, stirred until a uniform solution was formed, and the solution was heated in a 100 mL Teflon reactor at 140 ° C for 18 hours. After the reaction was completed, the precipitate was collected and repeatedly washed with deionized water. The obtained powder was mixed with Ketjen black (KB) and polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1 using isopropanol as a dispersant to prepare a slurry and rolled on a stainless steel net with a mesh size of 300. After drying at 80 ° C in air overnight, a slurry containing 3-4 mg cm -2 NVO electrode. After rolling, the positive electrode sheet was obtained, a Whatman diaphragm was used, the electrolyte was a 2 mol / L zinc sulfate solution, the soft package area was 5×6 cm, and the active material loading was 35 mg. The ammonium vanadate soft package battery assembled with the zinc negative electrode having a super hydrophobic and zinc-philic monolayer prepared in Example 1 was used as the experimental group, and the ammonium vanadate full battery assembled with pure zinc without any modification and the copper nanocluster-modified zinc negative electrode prepared in Comparative Example 1 was used as the control group. The above-assembled soft package full battery was tested at a current density of 1A g -1 The charge and discharge test is carried out under the conditions of Fig.11 As shown; in comparison, the long cycle stability of the matching super-hydrophobic monolayer zinc negative electrode battery prepared in Example 1 is more excellent, and the initial specific capacity is 186.0 mAh g -1After 200 cycles, it can still maintain 76.1% of its capacity, while the capacity retention rate of the zinc negative electrode battery matched with copper nanoclusters is as low as 52.5%, and the capacity retention rate of the pure zinc battery matched with it is 0 after 73 cycles, and the battery fails. This shows that the superhydrophobic monolayer can improve the interfacial stability of the zinc negative electrode, inhibit the side reactions mediated by water, and improve the electrochemical performance of the whole battery.
[0078] In addition, the same method as that of Test Example 1, Test Example 2, Test Example 3, and Test Example 4 was used to test the performance of the battery assembled with the zinc negative electrode obtained in each embodiment and comparative example. The performance data are shown in Table 1 below:
[0079] Table 1
[0080]
[0081] The results are analyzed. It can be seen from Test Examples 1-4 and Table 1 that the zinc negative electrode with super hydrophobicity and zinc-philic monolayer prepared in Examples 1-5 can stably exist under conditions such as bending, folding, and twisting. It can be seen from Examples 1-5 and Comparative Examples 5-6 that when the metal ion plating solution is a specific copper sulfate plating solution, indium chloride plating solution, or tin tetrachloride plating solution, the prepared zinc negative electrode with super hydrophobicity and zinc-philic monolayer has excellent performance in zinc-zinc symmetric batteries, ammonium vanadate full batteries, and ammonium vanadate soft-pack batteries, and the specific performance is that for zinc-zinc symmetric batteries, the impedance is lower and the current density is 1 mA cm -2 , capacity is 1 mAh cm -2 The cycle time under the conditions is greatly increased and the overpotential is greatly reduced; for the ammonium vanadate full battery, its initial specific capacity is not much different, but the capacity retention rate is greatly improved after 1500 cycles, and for the ammonium vanadate full battery, its initial specific capacity is not much different, but the capacity retention rate after 200 cycles is also greatly improved. That is to say, the present application uses a specific metal plating solution to maintain a certain roughness on the zinc metal surface under a reasonable immersion time and concentration and form metal nanoclusters modified zinc metal on the zinc metal surface. It is not applicable to all metal plating solutions that simply have a replacement reaction.
[0082] In addition, according to Examples 1-5 and Comparative Examples 2-4, the fluorosilane dispersion of the present application, when its solute is heptadecafluorodecyltrimethoxy(ethyl)silane, tridecafluorooctyltrimethoxy(ethyl)silane, dodecafluoroheptylpropyltrimethoxysilane, 1H,1H,2H,2H perfluorooctyltrimethoxysilane, heptadecafluorodecyltrimethoxy(ethyl)silane, the prepared zinc negative electrode with super hydrophobicity and zinc-philic monolayer has excellent performance in zinc-zinc symmetric batteries, ammonium vanadate full batteries and ammonium vanadate soft-pack batteries, while the effects of long-chain or short-chain fluorosilanes such as 3,3,3-trifluoropropyltriethoxysilane, triethoxy (1H,1H,2H,2H-nonafluorohexyl) silane and triethyl (trifluoromethyl) silane are relatively poor. That is to say, the present application selects some specific long-chain fluorosilanes, and not all long-chain fluorosilanes or short-chain fluorosilanes are applicable.
[0083] In addition, according to Example 1 and Comparative Example 1, it can be seen that in the absence of the subsequent action of the fluorosilane dispersion, the obtained zinc negative electrode exhibits poor performance in specific applications such as zinc-zinc symmetric batteries, ammonium vanadate full batteries, and ammonium vanadate soft-pack batteries, indicating that the metal ion plating solution treatment and the fluorosilane dispersion in the present application have a synergistic effect. In addition, it should be pointed out that if the zinc metal is not treated with a metal plating solution, since there is no metal nanocluster modification on the surface of the zinc metal, the subsequent fluorosilane dispersion will not show a hydrophobic phenomenon, so no relevant comparative example is made.
[0084] In summary, that is to say, the present application places zinc metal in a specifically configured metal ion plating solution and a fluorosilane dispersion, and after a suitable reaction time and concentration, the obtained zinc negative electrode with a super-hydrophobic, zinc-philic monolayer exhibits very excellent performance in a variety of batteries such as zinc-zinc symmetric batteries, ammonium vanadate full batteries, and ammonium vanadate soft-pack batteries.
[0085] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer, characterized in that: The method comprises: A metal ion plating solution is prepared, and zinc metal is immersed in the metal ion plating solution, and then the zinc metal is taken out, and repeatedly washed and dried to obtain zinc metal modified with metal nanoclusters; A fluorosilane dispersion is prepared, and the zinc metal modified by the metal nanoclusters is immersed in the fluorosilane dispersion. Then the zinc metal is taken out, and repeatedly washed and dried to obtain a zinc negative electrode with a super-hydrophobic and zinc-philic monolayer.
2. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 1, characterized in that The solute of the metal ion plating solution includes at least one of copper sulfate, indium chloride and tin tetrachloride, and the concentration of the metal ion plating solution is 0.1-0.5 mol / L.
3. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 2, wherein: In the step of immersing the zinc metal in the metal ion plating solution, then taking out the zinc metal, and repeatedly washing and drying to obtain the zinc metal modified with metal nanoclusters: The soaking time is 1 to 180 seconds, the drying time is 0.5 to 6 hours, and the oven temperature is 40 to 100°C.
4. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 1, characterized in that: The solute of the fluorosilane dispersion includes at least one of tridecafluorooctyltrimethoxysilane, heptadecafluorodecyltrimethoxysilane, dodecafluoroheptylpropyltrimethoxysilane and 1H,1H,2H,2Hperfluorooctyltrimethoxysilane, and the concentration of the fluorosilane dispersion is 0.01-0.2 mol / L.
5. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 4, characterized in that: In the step of immersing the zinc metal modified by the metal nanoclusters into the fluorosilane dispersion, then taking out the zinc metal, repeatedly washing and drying, to obtain a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer: The soaking time is 1 to 600 seconds, the drying time is 0.5 to 4 hours, and the oven temperature is 40 to 80°C.
6. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 1, characterized in that: The solvent of the fluorosilane dispersion includes at least one of ethanol, isopropanol, toluene, xylene, ethyl acetate, butyl acetate, acetone and methyl ethyl ketone.
7. The method for preparing a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to any one of claims 1 to 6, characterized in that: The super hydrophobic, zinc-philic monolayer is a chemically bonded modified layer.
8. A zinc negative electrode having a super-hydrophobic and zinc-philic monolayer, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of a zinc negative electrode having a super-hydrophobic and zinc-philic monolayer according to claim 8 in an aqueous zinc ion battery, characterized in that: The applications include: preparing a positive electrode sheet; The positive electrode sheet, Whatman glass fiber separator, electrolyte and zinc negative electrode with super hydrophobic and zinc-philic monolayer are assembled into a battery.
10. The use according to claim 9, characterized in that: The steps of preparing the positive electrode sheet include: ammonium vanadate, manganese dioxide, iodine, vanadium pentoxide, or polyaniline are mixed with carbon powder and then rolled or coated to obtain a positive electrode sheet; The step of preparing the electrolyte comprises: Dissolve ZnSO4·7H2O or Zn(OTf)2 in deionized water to prepare an electrolyte with a concentration of 1 to 5 mol / L.
